Improving Performance of Project through Utilizing Statistical Control Chart Based on Adaptive Management and Scientific Engineering - Nimr Nimr, Atheer Hashim; Naimi, Sepanta (International Journal of Intelligent Systems and Applications in Engineering, 2023)
the facade adaptive construction project management is considered a major challenge in project construction management. It represents one of the economic issues due to the use of sustainable concepts. This part of building construction in Iraq faced many problems. these problems are prepared as adaptive factors in this research. the questionnaire has been developed and evaluated by the experts. the main effective factors specified using the Weighted Decision Matrix method. The Weighted Decision Matrix Results observed for the economic adaptive factor is urbanization level effect, the socially effective factor is facility usage rate and the technologically effective factor is demand for construction equipment. Applying these factors effect on the performance of project can observe an enhancement in the project CPI. The enticement results show an improvement in CPI results. SPC control chart of CPI detects out-of-control limits and presents a signal of the necessity of corrective actions to dynamically anticipate project success, the current method provides an evolutionary monitoring and control model for project success that can be used to assess the strength of the relationship between factors and to model the interaction between variables.